Highly Educated Youths Are The Creators Of The Third Renaissance - Mamatkulov Shukhrat; Safarov Maksudali (Periodica Journal, 2025)
This article analyzes the priorities of state youth policy, important initiatives and reforms in Uzbekistan during the Third Renaissance. Attention to youth is considered one of the strategic foundations of the country's development. The conditions created by the state for young people, their role in education, professions, employment, innovative development and political activism are analyzed. Modern approaches and effective mechanisms for working with young people are also discussed
Keywords: Youth policy; Third Renaissance; education